2018
DOI: 10.1186/s13014-017-0949-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in 18F-borono-L-phenylalanine uptake in unresectable, advanced, or recurrent squamous cell carcinoma of the head and neck and malignant melanoma during boron neutron capture therapy patient selection

Abstract: BackgroundWe evaluated dynamic changes in 18F–borono-L-phenylalanine (18F–BPA) uptake in unresectable, advanced, or recurrent squamous cell carcinoma of the head and neck (SCC) and malignant melanoma (MM) during boron neutron capture therapy (BNCT) patient selection.MethodsDynamic changes in the maximum standardized uptake value (SUVmax), tumor-to-normal tissue ratio (TNR), and tumor-to-blood pool ratio (TBR) for 18F–BPA were evaluated in 20 patients with SCC and 8 patients with MM.ResultsSUVmax in SCC tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…As described in section “ Tumor accumulation of 18 F-FBPA and PET imaging ”, melanomas in animal models showed higher uptake of 18 F-FBPA than non-melanoma tumors, probably due to the trapping mechanism of 18 F-FBPA in melanogenesis. This melanoma-preferential uptake of 18 F-FBPA was confirmed clinically by Morita et al [ 85 ]. 18 F-FBPA showed a slight washout pattern in squamous cell carcinoma of the head and neck ( n = 20) and a persistent pattern in malignant melanoma ( n = 8).…”
Section: Clinical Studiessupporting
confidence: 56%
See 1 more Smart Citation
“…As described in section “ Tumor accumulation of 18 F-FBPA and PET imaging ”, melanomas in animal models showed higher uptake of 18 F-FBPA than non-melanoma tumors, probably due to the trapping mechanism of 18 F-FBPA in melanogenesis. This melanoma-preferential uptake of 18 F-FBPA was confirmed clinically by Morita et al [ 85 ]. 18 F-FBPA showed a slight washout pattern in squamous cell carcinoma of the head and neck ( n = 20) and a persistent pattern in malignant melanoma ( n = 8).…”
Section: Clinical Studiessupporting
confidence: 56%
“…Nariai et al indicated that in patients with malignant brain tumors the T / B ratio of 18 F-FBPA after a bolus injection of 18 F-FBPA had a significant linear correlation with the T / B ratio of 10 B estimated by 1-h constant infusion of 10 B-BPA, as simulated using the Runge–Kutta algorithm [ 84 ]. This type of quantitative evaluation has not been tried in other malignant tumors; however, Morita et al recently reported that the T / N ratios of 18 F-FBPA in head and neck cancers and malignant melanoma were not significantly changed over 120 min in spite of a slight decrease in 18 F-FBPA uptake [ 85 ]. In evaluating the T / N ratio of 18 F-FBPA in patients with head and neck cancers, it is notable that the uptake of 18 F-FBPA was higher in the dorsum tongue, submandibular gland, parotid gland, and tongue in this order among normal tissues in the oral and maxillofacial regions than in normal brain [ 86 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…18 F-BPA PET now has been widely used in patients with high-grade gliomas, , malignant meningioma, recurrent head and neck cancer, , and malignant melanomas in many investigations. This technology can accurately identify tumor lesions such as malignant brain tumors, which are difficult to judge by CT and MRI, and show the degree of malignant transformation.…”
Section: Imaging Methods Of Boron Macroimaging In Vivomentioning
confidence: 99%
“…Therefore, BNCT links two fundamental approaches, i.e., chemotherapy and traditional radiotherapy. L-p-boronophenylalanine (L-BPA) has been clinically used for different kinds of cancers including malignant melanoma (6)(7)(8), malignant brain tumors (1,9,10), recurrent head and neck cancer (3,11,12), and malignant mesothelioma (13,14). Unlike other radiotherapy, the cytocidal effect of BNCT on tumor tissue relies on the selective uptakes of boron compounds in the tumors.…”
Section: Introductionmentioning
confidence: 99%